Маргінальний персонаж у пошуках власного життєвого простору (на матеріалі роману Володимира Винниченка «Хочу!») - Дмитрук, В. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with one of the key features of modernistic outlook – «ambivalence» and its interpretation in Volodymyr Vynnychenko’s novel «I Want!». It is considered the basic form of the decision made by the protagonist in marginal situations. Special attention is paid to the peculiarities of the conflict situations as steps of development of the main hero. The ontologically psychological and boundary situation of modern style character in emotionally intense situation of the period is considered.